2020
DOI: 10.1111/jfd.13297
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of prophenoloxidase (proPO) gene in freshwater prawn, Macrobrachium rosenbergii, makes them susceptible to white spot syndrome virus (WSSV)

Abstract: Prophenoloxidase (proPO) is very important to protect the invertebrates from microbial infections. Our previous studies revealed that proPO was up‐regulated in WSSV‐injected Macrobrachium rosenbergii and is responsible for protecting M. rosenbergii from WSSV. In order to prove this mechanism, an attempt was made in the present study to silence the proPO gene in freshwater prawn by injection of dsRNA‐proPO followed by WSSV challenge. Two partial fragments of proPO with the size of 251 and 331 bp were used to sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…For example, in red swamp crayfish Procambarus clarkia , injection with the recombinant proPO2 could significantly decrease 65% mortality of WSSV-infected crayfish and reduced the amount of WSSV copy number in hepatopancreas and gill 28 . In addition, the silencing of the proPO gene in freshwater prawn Macrobrachium rosenbergi makes them susceptible to WSSV 29 . It was reported that the proPO gene was highly up-regulated after LPS stimulation, while the lack of LvSTAT down-regulated the proPO expression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in red swamp crayfish Procambarus clarkia , injection with the recombinant proPO2 could significantly decrease 65% mortality of WSSV-infected crayfish and reduced the amount of WSSV copy number in hepatopancreas and gill 28 . In addition, the silencing of the proPO gene in freshwater prawn Macrobrachium rosenbergi makes them susceptible to WSSV 29 . It was reported that the proPO gene was highly up-regulated after LPS stimulation, while the lack of LvSTAT down-regulated the proPO expression.…”
Section: Discussionmentioning
confidence: 99%
“…Results in the present study convey that optimum dietary thiamine levels signi cantly in uenced the activity of PO. In a study byThamizhvanan et al (2021), proPO gene-silenced freshwater prawn (Macrobrachium rosenbergii) showed 100% mortality in a challenge test exposing them to white spot syndrome virus (WSSV), while no mortality was observed in non-genetically modi ed shrimps injected with WSSV alone. It appears; therefore, the PO system is…”
mentioning
confidence: 99%